Associations of RANKL levels and polymorphisms with rheumatoid arthritis: A meta-analysis. - Young Ho Lee; Gwan Gyu Song (PLoS ONE, 2025)
Objectives This study examined the correlation between circulating receptor activator for nuclear factor-κB ligand (RANKL) levels and rheumatoid arthritis (RA), and investigated the association between polymorphisms in the RANKL gene and susceptibility to RA. Method We searched the Medline, Embase, and Cochrane databases for relevant publications up to September 2024. A meta-analysis was conducted to assess serum/plasma RANKL levels in patients with RA and controls, and to explore the relationship between RANKL rs9533156 and rs2277438 polymorphisms and RA susceptibility. Results Ten studies encompassing 1,682 RA patients and 1,288 controls were analyzed. RANKL levels were significantly higher in RA patients compared to controls (SMD = 0.665, 95% CI = 0.290-1.040, P = 0.001). Subgroup analysis affirmed these findings' consistency across different sample sizes and publication years. RANKL levels were positively associated with rheumatoid factor (RF) and Disease Activity Score-28 (DAS28) (RF correlation coefficient = 0.157, 95% CI = 0.028-0.282, P = 0.018; DAS28 correlation coefficient = 0.151, 95% CI = 0.125-0.370, P < 0.001). Additionally, the meta-analysis revealed significant associations between the susceptibility to RA and the RANKL rs9533156 C allele (OR = 0.609, 95% CI = 0.520-0.714, P < 0.010) as well as the rs2277438 G allele (OR = 1.206, 95% CI = 1.003-1.451, P = 0.047). These associations were consistent across homozygote comparisons and different genetic models. Conclusions This meta-analysis underscores the elevated circulating RANKL levels in RA patients and their significant correlation with RF and DAS28. Additionally, the RANKL rs9533156 and rs2277438 polymorphisms were significantly associated with RA susceptibility.